PENGARUH JOB SATISFACTION DAN JOB ENGAGEMENT TERHADAP KOMITMEN KERJA GENERASI Z - Nopiyanti, Anita; Supriadi, Yudi Nur; Valerie, Chiquita; Rofiq, Akmal; Zhafran, Irfan (Gapenas Publisher, 2024)
This study investigated the effect of job satisfaction and job engagement on the work commitment of generation Z in Agen Perjalanan Online. The results of the analysis showed that job satisfaction did not have a significant positive influence on work commitment, while work involvement had a strong and positive influence on work commitment. These findings are consistent with previous research showing that the relationship between job satisfaction and job commitment is often indirect and influenced by mediating factors. The research method used is a quantitative data approach with Structural Equation Modeling (SEM) analysis techniques based on Partial Least Square (PLS). The population studied was Online travel agency employees in DKI Jakarta, Indonesia, with a total of 50 respondents. The practical implication of these findings is the need to focus on strategies to increase employee engagement, taking into account basic psychological needs such as autonomy, competence, and social connectedness. Similarly, companies need to monitor and strengthen a positive and inclusive work environment to improve employee well-being and their overall productivity